A Broad Spectrum Protein Glycosylation System Influences Type II Protein Secretion and Associated Phenotypes in Vibrio cholerae - Vorkapic, Dina; Mitterer, Fabian; Pressler, Katharina; Leitner, Deborah R.; Anonsen, Jan Haug; Liesinger, Laura; Mauerhofer, Lisa-Maria; Kuehnast, Torben; Toeglhofer, Manuela; Schulze, Adina; Zingl, Franz G.; Feldman, Mario F.; et al. (Frontiers in Microbiology, 2019)
Protein secretion plays a crucial role for bacterial pathogens, exemplified by facultative human-pathogen Vibrio cholerae, which secretes various proteinaceous effectors at different stages of its lifecycle. Accordingly, the identification of factors impacting on protein secretion is important to understand the bacterial pathophysiology. PglLVc, a predicted oligosaccharyltransferase of V. cholerae, has been recently shown to exhibit O-glycosylation activity with relaxed glycan specificity in an engineered Escherichia coli system. By engineering V. cholerae strains to express a defined, undecaprenyldiphosphate-linked glycoform precursor, we confirmed functional O-linked protein glycosylation activity of PglLVc in V. cholerae. We demonstrate that PglLVc is required for the glycosylation of multiple V. cholerae proteins, including periplasmic chaperones such as DegP, that are required for efficient type II-dependent secretion. Moreover, defined deletion mutants and complementation strains provided first insights into the physiological role of O-linked protein glycosylation in V. cholerae. RbmD, a protein with structural similarities to PglLVc and other established oligosaccharyltransferases, was also included in this phenotypical characterization. Remarkably, presence or absence of PglLVc and RbmD impacts the secretion of proteins via the type II secretion system. This is highlighted by altered cholera toxin secretion, chitin utilization and biofilm formation observed in pglLVc and rbmD single or double mutants. This work thus establishes a unique connection between broad spectrum O-linked protein glycosylation and the efficacy of type II-dependent protein secretion critical to the pathogen's lifecycle.